A New Diamond Biosensor with Integrated Graphitic Microchannels for Detecting Quantal Exocytic Events from Chromaffin Cells. (12th July 2013) - Picollo, Federico; Gosso, Sara; Vittone, Ettore; Pasquarelli, Alberto; Carbone, Emilio; Olivero, Paolo; Carabelli, Valentina
<x xml:space="preserve">Abstract</x> An MeV ion‐microbeam lithographic technique can be successfully employed for the fabrication of an all‐carbon miniaturized cellular biosensor based on graphitic microchannels embedded in a single‐crystal diamond matrix. The device is functionally characterized for the in vitro recording of quantal exocytic events from single chromaffin cells, with high sensitivity and signal‐to‐noise ratio, opening promising perspectives for the realization of monolithic all‐carbon cellular biosensors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>